Modular System Recirculating Aquarium Management for Sustainable Ornamental Coral Production - Paharuddin, Paharuddin; Alham, Irawan; Sulkifli, Sulkifli; Ardiansyah, Ardiansyah; Jaya, Andi Asdar (LP2M INSURI Ponorogo, 2024)
Indonesian waters have potential ornamental coral resources in South Sulawesi waters, especially in Karanrang Island, which still need to be optimally utilized by the fishing community. The main objective of this community service is to increase the understanding and skills of the community in managing coral transplantation in situ and caring for them in an environmentally friendly modular system aquarium based on re-circulation. Adopting the ABCD (Asset-Based Community Development) method, this approach begins with the identification of local assets, including the expertise and skills of the karanrang island community. Subsequently, capacity building is carried out by utilizing these assets, and the community is actively involved in the planning and implementation process. Results included increased community knowledge on technological innovations of modular circulation systems holding aquarium design at the household scale and post-harvesting of coral transplant farming products for holding in aquariums. This process contributed to the development of the local ornamental coral sector, empowered the community, and opened up product marketing opportunities at both local and international levels.